2018
DOI: 10.5114/ada.2018.75237
|View full text |Cite
|
Sign up to set email alerts
|

Stress, itch and quality of life in chronic urticaria females

Abstract: IntroductionChronic urticaria (CU) belongs to a group of psychodermatological disorders, thus stress can play a significant role in this dermatosis onset and/or exacerbation. On the other hand, the disease itself accompanied by itch, may be a source of distress and could worsen patients’ quality of life (QoL).AimThe first goal of our study was to compare stress intensity between CU subjects and the control group. The second aim was to investigate the relationships between disease-related parameters (CU severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…For example, patients with psoriasis, alopecia, or urticaria were more hostile and neurotic than people with other dermatological conditions. Some authors have reported that subjects with urticaria have significantly interpersonal, depressed, more hysterical, and suspicious personality traits compared with controls [20,23,25].…”
Section: Results Discussionmentioning
confidence: 99%
“…For example, patients with psoriasis, alopecia, or urticaria were more hostile and neurotic than people with other dermatological conditions. Some authors have reported that subjects with urticaria have significantly interpersonal, depressed, more hysterical, and suspicious personality traits compared with controls [20,23,25].…”
Section: Results Discussionmentioning
confidence: 99%
“…Most participants indicated that psychological factors, such as stress at work or in their private lives, triggered their disease or worsened their symptoms. Indeed, patients with CU have demonstrated significantly higher stress levels compared to controls [ 21 ], and stress has been shown to exacerbate urticarial wheals [ 22 ]. Our findings underline the relevance of stress management and coping mechanisms in the treatment of patients with CU.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated associations between partner bereavement and chronic urticaria, alopecia areata and vitiligo in population‐based cohorts in settings with universal healthcare (UK and Denmark), using harmonized methodology. Previous studies have been limited by small sample size, difficulty in measuring stress, and potential misclassification of adverse life events due to recall bias . We undertook our study in two similar cohorts to enable replication, and used partner bereavement as a proxy for acute severe stress, with specific onset date.…”
Section: Association Between Partner Bereavement and Skin Disorders mentioning
confidence: 99%
“…Previous studies have been limited by small sample size, difficulty in measuring stress, and potential misclassification of adverse life events due to recall bias. [6][7][8] We undertook our study in two similar cohorts to enable replication, and used partner bereavement as a proxy for acute severe stress, with specific onset date. Limitations include a lack of information on the level and duration of stress arising from bereavement, individual responses to bereavement, social support, potential misclassification of partnership status, possible delay between disease onset and diagnosis, overrepresentation of severe cases in the Danish hospital setting, and absence (Denmark) and missingness (UK) of body mass index and lifestyle covariates.…”
Section: Referencesmentioning
confidence: 99%